1993
DOI: 10.1091/mbc.4.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor stimulates vascular endothelial growth factor production by human malignant glioma cells: a model of glioblastoma multiforme pathophysiology.

Abstract: Hypervascularity, focal necrosis, persistent cerebral edema, and rapid cellular proliferation are key histopathologic features of glioblastoma multiforme (GBM), the most common and malignant of human brain tumors. By immunoperoxidase and immunofluorescence, we definitively have demonstrated the presence of vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFr) in five out of five human glioma cell lines (U-251MG, U-105MG, D-65MG, D-54MG, and CH-235MG) and in eight human GBM tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
244
0
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(258 citation statements)
references
References 43 publications
11
244
0
3
Order By: Relevance
“…This Interactions between VEGF and other growth factors have already been described. EGF stimulates VEGF production in glioblastoma cells (Goldman et al, 1993), whereas TGF-b induces VEGF mRNA and protein in ®broblastic and epithelial cells (Pertovaara et al, 1994). VEGF synthesis is also increased by FGF-2 in rat vascular smooth muscle cells .…”
Section: Discussionmentioning
confidence: 99%
“…This Interactions between VEGF and other growth factors have already been described. EGF stimulates VEGF production in glioblastoma cells (Goldman et al, 1993), whereas TGF-b induces VEGF mRNA and protein in ®broblastic and epithelial cells (Pertovaara et al, 1994). VEGF synthesis is also increased by FGF-2 in rat vascular smooth muscle cells .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HeLa cells have been shown to posses high expression of EGFR, which appears to be driven by their intrinsic expression of the HPV proteins E6 and E7 (Hu et al, 1997). In addition, activation of the EGFR (growth factor/receptor) system has been shown to upregulate VEGF expression (Viloria-Petit et al, 1997;Detmar et al, 1994;Goldman et al, 1993;Gille et al, 1997). Therefore we hypothesized that in HPV positive cells upregulation of VEGF may be EGFR-mediated.…”
Section: Vegf Upregulation By Hela Cells Does Not Involve the Tgf A/ementioning
confidence: 98%
“…Other genetic changes might include additional virus-encoded products (such as E7) as well as other cellular oncoproteins. Regarding HeLa cells, we examined the possible contribution of the TGFa/EGF receptor signaling system due to its demonstrated over-activity in HeLa cells (Derynck et al, 1987;Hu et al, 1997) and also because EGFR activation can trigger VEGF expression (Viloria-Petit et al, 1997;Detmar et al, 1994;Goldman et al, 1993;Gille et al, 1997). However, using speci®c blocking antibodies to both TGFa and EGF receptor we showed that this receptorligand system is not involved in VEGF expression in HeLa cells.…”
Section: Hpv-16 E6 Oncoprotein and Vegf In Tumor Angiogenesismentioning
confidence: 99%
“…13,14 One consequence of upregulated EGFR tyrosine kinase activity is increased expression of proangiogenic factors, including VEGF, 15,16 which may lead to possible paracrine and autocrine stimulation of angiogenesis.…”
mentioning
confidence: 99%